2016
DOI: 10.1262/jrd.2015-118
|View full text |Cite
|
Sign up to set email alerts
|

Video tracking analysis of behavioral patterns during estrus in goats

Abstract: Here, we report a new method for measuring behavioral patterns during estrus in goats based on video tracking analysis. Data were collected from cycling goats, which were in estrus (n = 8) or not in estrus (n = 8). An observation pen (2.5 m × 2.5 m) was set up in the corner of the female paddock with one side adjacent to a male paddock. The positions and movements of goats were tracked every 0.5 sec for 10 min by using a video tracking software, and the trajectory data were used for the analysis. There were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
1
8
0
2
Order By: Relevance
“…The time spent for video-recording analysis is still in agreement with the most moderate time-consuming laboratory techniques used in the field. Development of an algorithm like that existing for specific behavioral studies in goat (Endo et al., 2016) and pig (Lind et al., 2005) could offer further opportunities to reduce the time spent in analyzing the recorded videos. Nevertheless, the present scoring technique is adequate to record accurately the daily LA rhythm in large animals and can perceive other behavioral phenomena that cannot be distinguished by an algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…The time spent for video-recording analysis is still in agreement with the most moderate time-consuming laboratory techniques used in the field. Development of an algorithm like that existing for specific behavioral studies in goat (Endo et al., 2016) and pig (Lind et al., 2005) could offer further opportunities to reduce the time spent in analyzing the recorded videos. Nevertheless, the present scoring technique is adequate to record accurately the daily LA rhythm in large animals and can perceive other behavioral phenomena that cannot be distinguished by an algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…A pesar de que el contenido de Na en dieta EWP (0.23% Na p/p, normosódica [Martus et al, 2005]) es ligeramente mayor que en el grupo control, el grupo EWP mostró una menor ingesta de alimentos comparado (Control: 21.95 ± 0.38 g; EWP: 18.63 ± 0.79 g) y, por consiguiente, un menor peso de heces (3.75 ± 0.13 g y 1.08 ± 0.07 g, respectivamente). Diversos factores pueden estar asociados al menor consumo de alimento como sabor y textura del alimento (Naim et al, 1986) (7)(8)(9)(10)(11)(12) 0/6 0/6 Modificar tratamiento (13)(14)(15)(16)(17)(18) 0/6 0/6 Detener experimento (19)(20)(21)(22)(23)(24)(25) 0/6 0/6 Motricidad (cm/s) 0.013 ± 0.002 0.015 ± 0.001…”
Section: Resultados Y Discusión Experimentounclassified
“…Cristians et al, 2019. A su vez, se debe considerar que la dieta EWP posee menor cantidad de potasio (K) y fibra que la dieta control, generando un (7)(8)(9)(10)(11)(12) 0/8 0/5 Modificar tratamiento (13)(14)(15)(16)(17)(18) 0/8 0/5 Detener experimento (19)(20)(21)(22)(23)(24)(25) 0/8 0/5…”
Section: Experimentounclassified
“…Here, upon sniffing and mounting, the female permits mounting by the male. These behaviors are generally monitored by a human observer because direct observation is currently regarded as the best method for obtaining detailed data regarding specific behaviors [7]. Generally, direct observation requires substantial effort and time, if the number of targets to be observed is large and the observations are to be conducted for a prolonged period.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [7] have shown that automated video tracking systems for studying animal behavior were introduced in the early 1990s and that they have been increasingly incorporated into studying laboratory mice [11][12][13] and other small animals. In addition to the development of digital image processing technology, several types of specialized computer software for animal tracking have been proposed, which allow tracking of positions and movement of subjects automatically and generate coordinates of a target position as time series data.…”
Section: Introductionmentioning
confidence: 99%